Alternate arm converters-based HVDC model compatible with the CIGRE B4 dc grid test system - Wickramasinghe, Harith R. (2020)
This paper develops an alternate arm converter (AAC)-based point-to-point high-voltage direct current (HVDC) transmission system compatible with the existing benchmark models of modular multilevel converter (MMC)-based HVDC and multiterminal dc (MTDC) grids. The developed AAC-based HVDC system expedites the future development of multi-converter, multiterminal benchmark models that enable the system level studies with detailed models of multiple topologies. The configuration and design parameters of the topology, are derived in alignment with the existing MMC-based benchmark systems. Detailed analysis and simulation studies based on real-time digital simulations verify the operation and performance of the developed AAC-based HVDC system and the associated control functions. The model developed in RTDS is also provided as supplementary material in order to enable further research and development on multiple topologies-based dc grids.